Effect of Wages and Incentives on Employee Performance of PT. Bank of North Sumatra, Lubuk Pakam Branch - Andri Prayogi (Journal of Economics and Business (JECOMBI), 2022)
Every company or agency in implementing programs that are directed is always efficient to achieve company goals. One way is to improve employee performance. Performance as a result of employee work is seen from the aspects of quality, quantity, working time, and cooperation to achieve the goals that have been set by the organization. The company's performance is said to be of quality and successful in achieving its objectives, which can be influenced by factors that come from within the company such as the competencies possessed by employees and employee work discipline and the provision of financial compensation in accordance with the ability of employees to complete their duties and responsibilities, resulting in output quality. PT. Bank of North Sumatra which is a source of businesses engaged in banking. The level of employee commitment in providing the best service will greatly affect the achievement of the goals of the company which in turn will lead to the growth of the bank. Banks are business entities whose growth is highly dependent on the amount of third party funds that are collected and channeled again to the public. This research was conducted with the aim to determine the effect of Wages and Incentives on Employee Performance of PT. Bank of North Sumatra, Lubuk Pakam Branch. This is to determine the effect of Intellectual Competence on Employee Performance at the Lubuk Pakam Branch of the Bank of North Sumatra. This is to determine the effect of Work Discipline on Financial Compensation at the Lubuk Pakam Branch of the Bank of North Sumatra. The results of this study are the wages and incentives given to PT. Bank Sumut, Lubuk Pakam Branch, to the employees of Bank of North Sumatra has a very good effect on improving employee performance. PT. Bank of North Sumatra has made all employees very welfare without prioritizing personal interests. Employee performance of PT. Bank Sumut Lubuk Pakam Branch has increased the provision of good wages and incentives at PT. Bank of North Sumatra, Lubuk Pakam Branch, 2020.